2018
DOI: 10.1520/acem20170049
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Uncertainty in the Master Curves of Viscoelastic Properties of Asphalt Concrete

Abstract: The prediction of asphalt concrete (AC) behavior using a continuum damage mechanics approach requires viscoelastic properties like creep compliance (CC) and relaxation modulus (RM) values. Because of practical limitations, dynamic modulus (DM) and phase angle (PA) measurements are used to construct CC and RM master curves. Numerous approximate interconversion techniques have been used for this purpose. Because of issues during testing, fabrication processes, and interconversion approximations, significant scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…According to Van Dijk et al’s research, fatigue life mainly depends on the dissipation modulus and energy consumption during the stress–strain cycle [ 34 ]. The mechanical properties of the asphalt mixture depend on how long the load is applied and the temperature when the pressure is applied [ 35 ]. Its complex modulus is composed of a storage modulus and loss modulus.…”
Section: Introductionmentioning
confidence: 99%
“…According to Van Dijk et al’s research, fatigue life mainly depends on the dissipation modulus and energy consumption during the stress–strain cycle [ 34 ]. The mechanical properties of the asphalt mixture depend on how long the load is applied and the temperature when the pressure is applied [ 35 ]. Its complex modulus is composed of a storage modulus and loss modulus.…”
Section: Introductionmentioning
confidence: 99%
“…Slowik characterized the measurement uncertainty for the stiffness modulus of the asphalt mixture using the indirect tension method ( 9 ). Rema discussed the uncertainty in interconversion methods from dynamic modulus test results to the creep compliance and relaxation modulus ( 10 ). Gudipudi studied the reliability of fatigue predictions in the simplified viscoelastic continuum damage model (S-VECD) given the variation in the input parameters ( 11 ).…”
mentioning
confidence: 99%
“…This uncertainty increases significantly as the loading rate becomes slower or as the temperature increases. Rema and Swamy studied various quantification methods to address the scatter in D ( t ) and E ( t ) ( 10 ). It was shown that AC can possess a significant scatter which is dependent on temperature and testing frequency.…”
mentioning
confidence: 99%